Comparative nutritional profile, fatty acid composition and in-vitro antioxidant properties of flour derived from four edible winged termite species from Uganda - Babirye Khadijah; Ammar Ahmad Khan; Shahrul Razid Sarbini (CyTA - Journal of Food)
Flour from four species of sun-dried edible winged termites was assessed and comparisons made in the proximate composition, fat extraction techniques, nutrient profiling, and in-vitro antioxidant properties. Pseudocanthotermes spriniger produced the significantly highest protein (57.96%) whereas Macrotermes subhyalinus plus Macrotermes bellicosus had the significantly highest fat content (18.60% and 18.92% respectively). Folch extraction method produced the highest crude fat yield (18.62% to 19.54%). M. bellicosus and P. spriniger produced the significantly highest isoleucine content whereas M. bellicosus and Odontotermes lateritius produced the significantly highest valine contents. M. bellicosus and P. spriniger produced the significantly highest oleic acid, whereas P. spriniger produced the significantly highest linoleic acid (3.81%). P. spriniger exhibited the significantly highest DPPH activity (56.27%) whereas M. bellicosus and O. lateritius showed the highest total phenolic content. Such a comparative study can help communities make more informed decisions on the most ideal termite species for a particular nutrition intervention.